MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MPMBS) - Sa'diyah, Rika -; Shofiyah, Siti; Siregar, Nurhidayah; ., Nurananda (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2019)
Management of school-based quality improvement (MPMBS) is a management model that gives greater autonomy to schools and encouraging participatory decision making directly involving all groups in school such as teachers, students, principals, employees, parents and communities to jointly improve the quality of schools according to the vision and mission that has been designed. Schools will have greater authority in managing the school if you get greater autonomy so that schools can be more independent. Schools are also becoming more able to develop programs that fit with the ideals and potential. Management of school-based quality improvement is part of a program of school-based management which is the antithesis of centralized management through decentralization programs in education and community participation is high. Autonomy was granted for school more freely manage all the resources to manage in accordance with the priority needs so that schools become more responsive to the needs of its users or the surrounding community.